2011
DOI: 10.2320/matertrans.mbw201010
|View full text |Cite
|
Sign up to set email alerts
|

Surface Analysis of Electrochromic Switchable Mirror Glass Based on Magnesium-Nickel Thin Film in Accelerated Degradation Test

Abstract: With the capability to change between reflective and transparent states, electrochromic switchable mirrors are expected to have numerous applications in optical devices, electronics devices and new energy-saving windows. If conventional windows can be adapted to incorporate switchable mirror technology, the solar radiation coming into a room could be effectively controlled, owing to features of the reflective state. Conventional windows are often subjected to environmental conditions such as high temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Additionally, an extra peak is observed at 646.3 eV, representing the satellite peak of the Mn 2p 3/2 main peak. Figure d displays the Mg 1s XPS spectrum. The peak at 1303.7 eV is associated with the chemical environment of Mg(1) in Mg(1)­(OH) 6 coordination. From the XPS diffraction patterns, it can be observed that there is only one environment for Mn and Mg throughout the entire crystal structure.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, an extra peak is observed at 646.3 eV, representing the satellite peak of the Mn 2p 3/2 main peak. Figure d displays the Mg 1s XPS spectrum. The peak at 1303.7 eV is associated with the chemical environment of Mg(1) in Mg(1)­(OH) 6 coordination. From the XPS diffraction patterns, it can be observed that there is only one environment for Mn and Mg throughout the entire crystal structure.…”
Section: Resultsmentioning
confidence: 99%